Can Internal, Cultural and Personal Factors Create A Culture of Innovation in SME in The Province of North Sulawesi? (Learning From COVID-19) - Roring, Ferdy; Maramis, Joubert B.; Sumual, Jacline Indirany; Kindangen, Wulan Deisy; Rompas, Wensy Frangky Israel (Universitas Dharma Wacana, 2023)
Many researches prove that SMEs (Small Medium Enterprises or SMEs) are thepillars of an economy. SMEs absorb a lot of labor and have a significant contributionto the economic growth of a country and region. SMEs also have a very large numberand are spread in every existing business sector, so SMEs receive serious attentionfrom both academics, researchers and the government. This study has a specificpurpose, namely to analyze and test the influence of perceived difficulties, responsesto difficuties, open-mindedness culture, creativity as well as adaptive ability),Individualism, power distance, uncertainty avoidance and masculinity / femininity),learning Capability (LC), Intellectual capital, Knowledge management, socialnetwork) on innovation culture, which is an aspect of originality or novelty in thisstudy. This study used a sample of SMEs in North Sulawesi Province and usedmultiple regression analysis techniques. The results of the analysis show thatperceived difficulties (X1), responses to difficulties (X2), open-mindedness culture(X3), creativity (X4) and adaptive ability (X5) have a significant effect (below 5%)on Innovation culture. The results of the analysis show that Learning Capability(LC) (X6), Intellectual capital (X7), Knowledge management (X8), social network(X9) have a significant effect (below 5%) on Innovation culture. The analysis resultsshow that Individualism (X10), uncertainty avoidance (X12) and masculinity /femininity (X13) have a significant effect (below 5%) on the culture of innovation.However, the power distance variable (X11) does not significantly affect the cultureof innovation. The results of the analysis show that the influence of perceiveddifficulties (X1), responses to difficulties (X2), open-mindedness culture (X3),creativity (X4) and adaptive ability (X5) has a significant effect (below 5%) oninnovation culture, remains significant even though it has been controlled for aspectsof the owner's age, ethnicity and business age. The results of testing the effect ofinternal factors (Learning Capability (LC) (X6), Intellectual capital (X7),Knowledge management (X8), social network (X9) on innovation culture (Y), showdifferent results specifically on the Learning Capability (LC) variable (X6), wherewhen controlled for aspects of ethnicity and business age, this variable becomesinsignificant on innovation culture. For the results of testing the effect of culturalcultural factors (Individualism (X10), power distance (X11), uncertainty avoidance(X12) and masculinity / femininity (X13) on innovation culture (Y), with variablecontrol of owner age, ethnicity and business age, no impact on innovation culture.